Ball, The Cold War - An International History 1947-1991 - Theilmann, John (Teaching History: A Journal of Methods, 2000)
Now that the Cold War is "history," a spate of works are appearing that take advantage of newly available documents and memoirs. Teachers of twentieth-century diplomatic history and post-1945 U.S. history need, in particular, a solid text that lays out the basics of the Cold War as well as indicates the scope of scholars' opinions.